SOHO Revue - ABSOLUT. (Praag : SOHO, 1992)
Fonds Suzan Daniel (FSD)
Periodiciteit : ?
Redactie : Blanickà 16, 12000 Praha 2 ; vanaf (1993) : Vinohraskà 46, 12041 Praha 2
Vanaf (1999) 1: ABSOLUT - SOHO Revue
Periodiek